2008
DOI: 10.1051/fruits:2008007
|View full text |Cite
|
Sign up to set email alerts
|

Budbreak, fruit quality and maturity of ‘Superior’ seedless grapes as affected by Dormex®under Jordan Valley conditions

Abstract: Budbreak, fruit quality and maturity of 'Superior' seedless grapes as affected by Dormex ® under Jordan Valley conditions. Abstract-Introduction. In subtropical regions, the lack of or insufficient winter chilling has been one of the most important yield-limiting factors for table grapes. Winter chilling for several weeks is required to cause the transition of both vegetative and floral buds from the dormant to the active state. Thus, the effect of time of application of Dormex ® (hydrogen cyanamide) on fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Actress random samples of 6 bunches per vine were harvested when SSC reached about 16-17% according to Muhtaseb and Ghnaim (2007). The following characteristics were determined: -Yield/vine (kg) was estimated as number of bunches /vine multiplied by average bunch weight /vine and average estimated yield /vine was calculated.…”
Section: Yield and Physical Characteristics Of Bunchesmentioning
confidence: 99%
“…Actress random samples of 6 bunches per vine were harvested when SSC reached about 16-17% according to Muhtaseb and Ghnaim (2007). The following characteristics were determined: -Yield/vine (kg) was estimated as number of bunches /vine multiplied by average bunch weight /vine and average estimated yield /vine was calculated.…”
Section: Yield and Physical Characteristics Of Bunchesmentioning
confidence: 99%
“…Similarly, Hyun et al, (1996) also found the higher bunch weight was recorded with ethephon treatments applied at veraison in "Kyoho" grapes. Muhtaseb and Ghnaim (2008) studied the effect of time of application of Dormex®. They found that Dormax treated vines had significantly higher fruit weight.…”
Section: Bunch Weight (G)mentioning
confidence: 99%
“…The vines treated with Dormex (Hydrogen Cyanamide) broke bud 4-26 days earlier than the control. All vines that had been trimmed and given the Dormex treatment began to flower 55-64 days following the pruning, 4-13 days earlier than the control [17]. However, the period of maturity was only accelerated by 4 days when the same concentration was applied 53 days before natural bud break.…”
Section: Effect Of Hydrogen Cyanamide On Duration and Uniform Bud Bre...mentioning
confidence: 98%
“…In addition, more TSS was detected from vines treated with Hydrogen Cyanamide (H2CN2) throughout every harvesting date as compared to the control. However, the TSS level of the fruit was modest or unaffected by delaying Hydrogen Cyanamide (H2CN2) treatment for longer than two weeks after pruning [17].…”
Section: Yield and Qualitymentioning
confidence: 99%